2022
DOI: 10.3390/land11081269
|View full text |Cite
|
Sign up to set email alerts
|

Between Plain and Plateau: Micro-Transitions in Zooarchaeological Landscapes in the Guanzhong Region of Northwest China

Abstract: Transitions in animal exploitation patterns are caused by topographical and climatic variations on both macro and micro scales. This paper presents temporally and spatially contextualized faunal profiles from 27 sites in the Guanzhong (关中) region of Shaanxi province (陕西省), PRC which date from the Early Neolithic to the Bronze Age (ca. 6000–1000 BCE). Climatic and environmental data was cross-referenced with archaeological, archaeobotanical and (where appropriate) historical sources to examine the reasons for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…In Central Shaanxi pigs were domesticated relatively early, probably in the Mid-Neolithic (Barton et al, 2009), and their importance grew during the Yangshao and Longshang periods (Hu, 2001;Hu et al, 2011;Wang et al, 2013). A slight, though steady, increase in bovids, at the expense of pigs, has been documented from the end of the Longshan period (Hu, 2001;Hu et al, 2008;Hu et al, 2016), and according to our results, became more dramatic in the late second millennium BCE (for a summary see Festa and Monteith (2022)).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In Central Shaanxi pigs were domesticated relatively early, probably in the Mid-Neolithic (Barton et al, 2009), and their importance grew during the Yangshao and Longshang periods (Hu, 2001;Hu et al, 2011;Wang et al, 2013). A slight, though steady, increase in bovids, at the expense of pigs, has been documented from the end of the Longshan period (Hu, 2001;Hu et al, 2008;Hu et al, 2016), and according to our results, became more dramatic in the late second millennium BCE (for a summary see Festa and Monteith (2022)).…”
Section: Discussionsupporting
confidence: 80%
“…While caprines and cattle are fairly tolerant of arid conditions, pigs require a plentiful and dependable supply of water (Burrin, 2001). Also, under cold and arid conditions, agricultural productivity would have declined, prompting a wider and more diversified use of the landscape, including the expansion into marginal lands, which would have been easier with bovid herding (Festa and Monteith, 2022). An et al (2005) and Huang et al (2004) have shown that climatic deterioration in the Loess Plateau caused many rain-fed Degerbol and Fredskild (1970) and Russel (1993), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zooarchaeological research on this region has been carried out most fully in China (Yuan, 2015), with over 20 sites have been systematically studied, providing rich datasets for us to discuss meat procurement strategies. Recognizing the importance of this region, researchers have recently shifted their focuses towards subsistence economy in Guanzhong (e.g., Zhao and Chen, 2011;Qu et al, 2018;Zong et al, 2021;Festa and Monteith, 2022). However, there is still a number of the sites that have not been covered by their datasets and a lack of discussion on the relationship between the regional subsistence economy and the corresponding societal development.…”
Section: Introductionmentioning
confidence: 99%